PENTINGNYA BERTUTUR KATA-KATA YANG BAIK, SOPAN, DAN POSITIF SEBAGAI wujud TINGKAH LAKU YANG MULIA DALAM MEMBERIKAN PUJIAN ATAS KINERJA, KARYA, DAN PRESTASI - Bachtiar, Ferdiansyach Romero (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
Language has a fundamental role in human life, not only as a means of communication, but also as a reflection of a person's character, attitude, and noble conduct. Good, polite, and positive speech can strengthen social relationships, increase motivation, and maintain harmony in daily interactions. One concrete form of positive speech is praise. Sincere praise for one's appearance, work, or achievements can increase self-confidence, motivation, and enthusiasm to continue developing. This article is prepared through a literature review by examining various sources, including books, national and international journals, and lecture materials related to noble conduct. The discussion focuses on the importance of positive speech in giving praise for performance, work, and achievement, with reference to theories of psychology, communication, and character education. Theories used include Maslow, Herzberg, DeVito, Lickona, Fredrickson, Seligman, Deci & Ryan, as well as contemporary research on positive emotions and appreciation. The results show that praise plays an important role in creating a healthy academic and professional atmosphere, strengthening social bonds, and supporting the formation of a positive organisational culture. However, praise must be given proportionally and sincerely so as not to create a manipulative or excessive impression. Thus, getting into the habit of saying kind words, being kind, and being sincere can help to build a positive organisational culture. However, praise must be given proportionally and sincerely so as not to create a manipulative or excessive impression. Thus, getting used to saying kind, polite, and positive words is a real form of noble conduct that is relevant in personal, academic, and work life.